2015
DOI: 10.1037/gdn0000026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of client feedback in group psychotherapy.

Abstract: Monitoring progress in psychotherapy routinely (i.e., client feedback) has yielded positive results for improving both outcome and retention in individual and couple therapy; however, evidence of client feedback efficacy in a group format is limited. Using a randomized cluster design, group therapy participants (N = 84) were assigned to a client feedback or treatment-as-usual (TAU) condition in a university counseling center. Clients in the feedback condition used the Partners for Change Outcomes Management Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 104 publications
1
61
4
Order By: Relevance
“…The numbers on the ORS and SRS had no normative meaning and were only related to the client's specific circumstance. Over time, psychometric studies were published (e.g., Duncan et al, 2006;Miller et al, 2003), five RCTs completed resulting in PCOMS designation as an evidence-based practice (Anker et al, 2009;Reese et al, 2009;Reese et al, 2010;Schuman et al, 2015;Slone et al, 2015), a cohort study with children, caregivers, and teachers (Cooper et al, 2012), two benchmarking studies demonstrating effectiveness in public behavioral health , and hundreds of thousands of administrations analyzed to create expected treatment response trajectories.…”
Section: Both/andmentioning
confidence: 99%
“…The numbers on the ORS and SRS had no normative meaning and were only related to the client's specific circumstance. Over time, psychometric studies were published (e.g., Duncan et al, 2006;Miller et al, 2003), five RCTs completed resulting in PCOMS designation as an evidence-based practice (Anker et al, 2009;Reese et al, 2009;Reese et al, 2010;Schuman et al, 2015;Slone et al, 2015), a cohort study with children, caregivers, and teachers (Cooper et al, 2012), two benchmarking studies demonstrating effectiveness in public behavioral health , and hundreds of thousands of administrations analyzed to create expected treatment response trajectories.…”
Section: Both/andmentioning
confidence: 99%
“…The general aim of the present study was to investigate the ability of the OQ-Analyst to predict dropout from an inpatient SUD treatment. Dropout is often linked to deterioration, 44 and the OQ-Analyst use the same prediction model to predict both outcomes. Based on studies addressing the OQ-Analyst ability to predict deterioration, 2934 we hypothesised that the system would be able to predict a more frequently occurring event such as dropout, above the level of deterioration, that is above a hit rate of 85%.…”
Section: Discussionmentioning
confidence: 99%
“…While identifying patients with psychosocial distress impacting their health and well-being is an important function of primary care screening tools, their use as a quality improvement intervention has not been demonstrated. The PHQ-9, for example, has been shown to be a valid tool for monitoring clinical change over time (Löwe et al ., 2004), but has not been empirically demonstrated to improve patient outcomes (Gilbody et al ., 2008; Fuchs et al ., 2015). The PCOMS feedback intervention has been demonstrated to improve patient outcomes in five randomized clinical trials (Anker et al ., 2009; Reese et al ., 2009; 2010; Shuman et al ., 2015; Slone et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple validation studies of the ORS (Miller et al, 2003;Bringhurst et al, 2006;Campbell and Hemsley, 2009;Reese et al, 2012) as well as efficacy studies have found that the ORS generates reliable scores. Coefficient αs have ranged from 0.87 to 0.91 in validation studies and from 0.82 (individual therapy) (Reese et al, 2009) to 0.92 (group therapy) (Slone et al, 2015) in clinical studies. Concurrent validity of the ORS has found moderately strong correlations with other validated measures (Miller et al, 2003;Bringhurst et al, 2006;Campbell and Hemsley, 2009;Gillaspy and Murphy, 2011).…”
Section: Methodsmentioning
confidence: 99%